2007
DOI: 10.1590/s0101-20612007000200022
|View full text |Cite
|
Sign up to set email alerts
|

Resíduos do beneficiamento do camarão cultivado: obtenção de pigmentos carotenóides

Abstract: A extração de pigmentos carotenóides constitui uma possível alternativa, de grande agregação de valor, para o aproveitamento da cabeça do camarão Litopenaeus vannamei. O objetivo do presente trabalho foi a identificação, a extração e a quantificação dos principais pigmentos desta matéria-prima, coletados a partir de uma planta de beneficiamento de camarão no Ceará -Brasil. Após cocção dos resíduos a 100 °C, na proporção 1:2 cabeça de camarão e água durante 15 minutos, obteve-se uma pasta de pigmentos brutos ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 10 publications
(12 reference statements)
0
13
1
1
Order By: Relevance
“…Protein content in the flour was lower than that found by Lima et al (2007), which was 66.01% for shrimp cephalothorax flour. Sriket et al (2007) found 18.8% protein content in shrimp fillets, a value close to that found in fresh cephalothorax examined in the present research.…”
Section: Resultscontrasting
confidence: 66%
See 2 more Smart Citations
“…Protein content in the flour was lower than that found by Lima et al (2007), which was 66.01% for shrimp cephalothorax flour. Sriket et al (2007) found 18.8% protein content in shrimp fillets, a value close to that found in fresh cephalothorax examined in the present research.…”
Section: Resultscontrasting
confidence: 66%
“…Microbiological analyses were performed in triplicate, in the Laboratory of Microbiology, Department of Nutrition, at Universidade Federal da Paraíba, using the methodology described by Vanderzant & Splittstoesser Crustacean residues, depending on the species and type of processing, can amount to 85% of the initial weight (Ogawa et al, 2007). According to Cavalheiro et al (2007), the low use of this by-product remains a serious problem, contributing to the overall cost of production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the fact that the SFE provides much higher astaxanthin content compared to the SOX sample, the biological potential of the astaxanthin natural form (from both shrimp extracts) could also be high. For instance, natural astaxanthin show an antioxidant potential higher than other components (10 times superior of the zeaxanthin, lutein and ␤-carotene [44]) and also protective effect against UV-radiation [24], antitumor [45], among other biological properties. treatment.…”
Section: Extracts Compositionmentioning
confidence: 99%
“…After the fourth day of growth, the elevation in OG concentration was attributed to the bacterial oxycarotenoids produced by that time. R. gelatinosus oxycarotenoids derive from terpenoid compounds (Margalith 1992;Ausich 1997;Breithaupt 2007;Ogawa et al 2007) and, due to their lipid character, they probably were solubilized in hexane and extracted together with oils and greases, since biomass was not removed from substrate before this analysis too. So, the mean decrease in OG content during the growth period was of 47.71%, but better results probably would be found if cell mass had been removed from cultures for sampling.…”
Section: Characteristics Of the Bacterial Growthmentioning
confidence: 99%